Collecting and Directing Correct Qur’anic Readings in Al-Baidawi Explanations' (d.685 AH) Surat Al'anbia' as a Model (Islamic Sciences Journal, 2023)
Praise be to Allah, the praise of the thankful, and blessings and peace be upon the most honorable of the prophets and messengers, our master Muhammad, and upon all his family and companions. And after ...Because the sciences, even if their origins differ, and their variants vary, then the greatest of them is a matter, the highest mentioned, and the most expensive of which is a dowry that relates to the great Qur’an the best book and the greatest book, and there is no doubt that the science of readings is the most science related to the Book of God it is an honorable science, and an honorable demand, even if knowledge is an honor for the known. ; It derives its sources from the revelation of Allah revealed through our master Gabriel, peace be upon him, to the first teacher of the readings, our master Muhammad. From this point of view, this research is specialized in the correct readings in the interpretation of Imam al-Baidawi (may God have mercy on him) and his name is (collecting and directing the correct Qur’anic readings in Tafsir al-Baidawi) (D.685 AH) Surat Al-Anbiya as a model).